First record of Heteropsylla caldwelli Burckhardt (Hemiptera: Psyllidae) from Brazil and its population dynamics on earpod tree in Rio Grande do Sul. - MACHADO, L. M. (2017)
Heteropsylla caldwelli Burckhardt (Psyllidae, Ciriacreminae) is reported for the first time from Brazil(States of Minas Gerais, Paraná, Rio Grande do Sul) from Enterolobium contortisiliquum (Vell.) Morong.The earpod tree, from Albizia edwallii (Hoehne) Barneby and J.W. Grimes and Senegalia polyphylla (DC.)Britton (Fabaceae, Mimosoideae), all previously unknown hosts. The population dynamics of the psyllidwere investigated in a seven-year-old plantation of E. contortisiliquum in an abandoned open-pit coal minein Candiota, Rio Grande do Sul during two years. The population showed peaks in spring and summer,correlating directly with the mean air temperature and the population size of microhymenoptera.